Effect of the retro-filling process on kraft paper and gasket materials in transformers - Nor Hidayah Rahim; Imran Sutan Chairul; Sharin Ab Ghani; Mohd Shahril Ahmad Khiar; Arfah Syahida Mohd Nor; Farrah Salwani Abdullah (Bulletin of Electrical Engineering and Informatics, 2026)
Mineral oil (MO) is the most widely used insulating liquid in oil-filled transformers. Numerous studies have investigated the use of alternative synthetic and ester-based insulating oils as replacements for MO. However, the effects of the retro-filling process on transformer materials remain insufficiently explored. This study examines the impact of retro-filling and thermal ageing on transformer kraft paper and gasket materials. Kraft paper strips, fluoroelastomer (FE) and nitrile butadiene rubber (NBR) gaskets, MO, synthetic oil (SO), and ester oil (EO) are used in the investigation. Initially, three sample bottles containing MO undergo thermal ageing for 200 hours at 130 °C. Subsequently, the retro-filling process is performed using MO, SO, and EO respectively. The samples are then subjected to an additional 200 hours of ageing at the same temperature. Results indicate that EO demonstrates superior performance in terms of shore hardness (+1.06%), while SO better preserves the tensile strength of kraft paper strips. These findings suggest that the retro-filling process can contribute to extending the service life of transformers.